Soil organic carbon and particulate carbon in water in riparian systems under different land use - Guerra-Hernández, Eloísa A.; Cruz-Flores, Gerardo; Etchevers-Barra, Jorge D. (REVISTA TERRA LATINOAMERICANA, 2021)
Overexploitation of hydric resources and lack knowledge of interactions between riparian vegetation, water and soil, generates loss of environmental services and ecological degradation in many mountainous riparian environments. In order to characterizing riparian-soils and non-riparian soils, soil organic carbon content and particulate carbon was evaluated as ecological degradation indicators and also degree of association between physical and chemical water properties with those of riparian soils. Twenty sites were selected in lotic systems between 1900-3900 m on slopes Western in Iztaccíhuatl-Popocatépetl National-Park and influence zone. Also variability soil organic carbon content was evaluated at 1 and 5 m from stream (riparian soils) and also at more than 5 m from river (non-riparian soils) in different types of land use. Results showed signif icant relationships between soil organic carbon, electrical conductivity, pH, total nitrogen and available phosphorus with water properties (temperature, pH, conductivity, nitrates, ammonia, total phosphorus, dissolved oxygen, biochemical oxygen demand and particulate organic carbon). An inverse relationship was observed between soil organic carbon content of with particulate organic carbon, nitrates and nitrites, conductivity and dissolved oxygen. No signif icant differences were found in riparian-soils organic carbon (1 and 5 m), but there were signif icant differences in non-riparian soils organic carbon. Both soil organic carbon and water organic carbon particulate contents showed signif icant differences with respect to land use. Organic carbon contents in preserved riparian soils were higher than 240 Mg SOC ha-1 but in riparian-soils of degraded sites almost f ifty times smaller (5 Mg SOC ha-1).